Soil characteristics of post-mining reclamation land and natural soil without top soil - Desi Nadalia; Heru Bagus Pulunggono (Brawijaya University, 2020)
Generally, Nickel mining was conducted by the open-pit mining method which caused change of soil physical, chemical and biological properties. Reclamation land often experienced various obstacles, including microclimate conditions that were not yet suitable, overburden chemical, physical and biological properties, difficulty in obtained ameliorant, and lack of topsoil. Topsoil that was used for post-mining reclamation land activities was obtained from the soil is not yet mined locations (natural soil). This study was aimed to determine differences in soil characteristics (soil physical, chemical and biological properties) on post-mining reclamation land with natural soil without topsoil. The research used survey methods conducted on post-mining land of PT. INCO. Soil samples were taken at 2 locations, namely, the location of post-mining reclamation (Harapan) and location that had not mined but the topsoil had peeled to a depth of ± 1 meter (Shelly). The results showed that the soil physical and biological properties at Shelly location were relatively better than those at Harapan location. The soil at Harapan and Shelly locations had available P content and exchangeable-Na was low and exchangeable-Ca was very low. Exchangeable-Mg was high at Harapan, while at Shelly was low-moderate. The exchangeable-K content of the soil in the Harapan location was moderate than Shelly location. The soil at Harapan location had a very high Base Saturation (BS) with a pH of 6.7 than Shelly location had high BS with a pH of 5.8. It is necessary to improve post-mining reclamation land management.